Effects of Isoflavone Intake on Energy Requirement, Satiety, and Body Composition of Neutered Adult Cats - Ana Lúcia Yoshida da Silva Yamada; Mônica Estela Zambon Merenda; Layne Carolina Pereira; Nayara Maira Dalgallo Bonneti; Isabela de Oliveira Martins; Alina Stadnik Komarcheuski; Lucas Ben Fiuza Henríquez; Eduardo Kato Watanabe; Guilherme Bernardo Cornélio Coelho; Vanderly Janeiro; Nilva Maria Freres Mascarenhas; Ricardo Souza Vasconcellos (Animals)
Isoflavones are composed of phytoestrogens (genistein and daidzein), which can be metabolized by cats. These compounds can promote the maintenance of lean body mass and control food intake. These effects are desirable in neutered animals, as they are predisposed to obesity. The objective of this study was to evaluate the effects of dietary supplementation of 1.0% isoflavone on the metabolizable energy intake, serum concentrations of satiety-related hormones and peptides, and body composition of neutered cats. Sixteen neutered adult cats were blocked by gender and divided into two groups (n = 8): the control group (CG) received a commercial diet, while the isoflavone group (IG) received the same diet supplemented by 1% of isoflavone for 99 days. Computed tomography was performed on the first and last experimental days to assess the animals’ body composition. Satiety challenges were conducted on days 19 and 44. In the last day of the study, blood samples were collected to determine the concentration of insulin, ghrelin, leptin, peptide YY, and GLP-1. A statistical analysis was conducted using R software 3.5.2, considering both the interaction and individual effects of group and time (p < 0.05). The average intake of genistein in the IG was 0.75 ± 0.10 mg/kg body weight, and daidzein intake was 51.73 ± 7.05 mg/kg. No significant individual or interaction effects were observed for any of the analyzed variables. Therefore, the inclusion of 1.0% isoflavone in the diet did not affect the energy requirements, satiety responses, or body composition of neutered adult cats.